An Approach to the Rhetoric of Boebert and Díaz-Ayuso’s Political Tweets on X: A Corpus-Assisted Analysis - María Milagros del Saz Rubio (Revista Alicantina de Estudios Ingleses)
This article presents a corpus-assisted analysis of the rhetoric employed in the political tweets of Lauren Boebert and Isabel Díaz-Ayuso on the micro-blogging site X (formerly Twitter). This study adopts the analytical framework Appraisal Theory (Martin & White, 2005), to explore how these politicians utilize negativity as a strategic tool to discredit and weaken their adversaries. The research identifies key motifs and evaluative strategies within their tweets, illustrating the role of negativity in political discourse. Findings reveal that both politicians direct their negativity toward their political rivals, viz., presidents Joe Biden and Pedro Sánchez, while channeling it towards immigrants and independentist parties. Amongst the evaluative resources most commonly deployed, Lauren Boebert and Isabel Díaz-Ayuso utilize inscribed negative judgments of propriety and veracity to accuse their rivals based on their lack of morality and truthfulness regarding various policy issues. The qualitative study has also revealed that politicians present their stances through monoglossic formulations that leave no room for argumentation and debate. This idea reinforces that even if their negativity is not intended as a polarizing agent, it may affect the potential electorate. This study contributes to understanding the dynamics of online political communication, highlighting the implications of negativity in shaping public opinion and political narratives.